Crude extracts of two different leaf plant species and their responses against subterranean termite Coptotermes formosanus - YULIATI INDRAYANI; MUSRIZAL MUIN; TSUYOSHI YOSHIMURA (Nusantara Bioscience, 2016)
Abstract. Indrayani Y, Muin M, Yoshimura T. 2016. Crude extracts of two different leaf plant species and their responses against subterranean termite Coptotermes formosanus. Nusantara Bioscience 8: 226-231. Crude extracts of plants consist of various chemical compounds useful for many purposes and their effects depend on the comprising active ingredients and applied concentrations. This study was conducted to determine the chemical compounds of plant leaf extracts and examine their responses against subterranean termite Coptotermes formosanus Shiraki. Two tropical plant species [clove (Syzygium aromaticum) and cajuput (Melaleuca leucadendra)] were extracted with 70% ethanol solvent. As the two different plant crude extracts contain eugenol, though to have termiticidal performance, various concentrations (0.1%, 0.05%, and 0.01%) based on their eugenol contents were prepared with filter paper samples for the test. The termite mortality and mass loss of extract-treated and untreated control filter paper samples were determined after four weeks of exposure. Results showed that crude extracts of different plant species showed different responses against the subterranean termites although they were applied at the same eugenol-based concentration. At the concentration of 0.1%, the crude extract of S. aromaticum caused termite mortality and consumption rates of 100% and 0.3%, respectively. Whilst, the crude extract of M. leucadendra caused significantly lower termite mortality (36.8%) and higher consumption (9.1%). Samples with lower eugenol-based concentration showed lower termite mortality and may have attractive effects on termites as indicated by higher consumption at the concentration of 0.01% compared to untreated controls. These results suggested that crude extracts of different two leaf species had different effects on subterranean termite C. formosanus even though they were applied at the same eugenol-based concentrations.